Religious Court Dispensation on Applications for Child Marriage License in Islamic Law Perspective (Study of the Luwuk Religious Court) - Citra Dewi; Maisa; Andi Purnawati (Program Pascasarjana Universitas Muhammadiyah Palu, 2022)
The dispensation for child marriage granted by the judge in the religious court is a provision of Law Number 16 of 2019 concerning Marriage. It states that the age limit for marriage for boys and girls is the same, which is 19 years. Then when examined from the perspective of Islamic law based on the compilation of Islamic law (KHI), it does not set a standard age for marriage. The research was conducted at the Religious Courts of Luwuk Regency, the Office of Religious Affairs (KUA) of North Luwuk District, and the Kilongan Village Office. The research was carried out in June – July 2022. The research source was the head of the Office of Religious Affairs (KUA) Kec. North Luwuk, the young clerk of the Luwuk Religious Court application, and the secretary of the whole kilongan. Based on the results of the research obtained above, the researchers found that the dispensation against child marriage permits from the perspective of Islamic law should still prioritize Islamic values ​​but not override the laws and regulations that apply in Indonesia, meaning that society in general and parents in particular observant to see the principle of benefit in marrying off their children at an age that is not yet mature enough according to the law. The researcher's suggestions are (1) In granting marriage dispensation permits to children, of course, still pay attention to the principle of benefit that comes from Islamic law itself, namely, the purpose of marriage, the benefits of marriage, and the nature of marriage. (2) To form a firm and careful attitude of a judge, it requires emotional maturity of a judge who handles a marriage dispensation application.